1996
DOI: 10.1128/aac.40.6.1412
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of quinolones, beta-lactams, tobramycin, and trimethoprim-sulfamethoxazole against nonfermentative gram-negative bacilli

Abstract: From 1991 to 1995, 8,975 nonfermentative gram-negative bacilli were isolated from patients at The Ohio State University Medical Center: 71% Pseudomonas aeruginosa, 14% Stenotrophomonas maltophilia, 7.6% Acinetobacter baumannii, and <2% each of 25 other species. The MICs of trovafloxacin (CP-99,219), ciprofloxacin, ofloxacin, ampicillin-sulbactam, piperacillin, piperacillin-tazobactam, ceftazidime, cefoperazone, ceftriaxone, imipenem, tobramycin, and trimethoprim-sulfamethoxazole (TMP-SMZ) were determined for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 20 publications
2
37
0
2
Order By: Relevance
“…In our strains, MIC 50 and MIC 90 to imipenem were high (4 and 8 mg/l, respectively), and proved similar to those observed by other authors [26,[31][32][33], although higher than those reported in many studies [23][24][25]27,[34][35][36][37][38]. However, significant discrepancies were found among the various biotypes, with noticeably lower MIC for biotypes 9 and 18 than for biotypes 1 and 2.…”
Section: Resultssupporting
confidence: 90%
“…In our strains, MIC 50 and MIC 90 to imipenem were high (4 and 8 mg/l, respectively), and proved similar to those observed by other authors [26,[31][32][33], although higher than those reported in many studies [23][24][25]27,[34][35][36][37][38]. However, significant discrepancies were found among the various biotypes, with noticeably lower MIC for biotypes 9 and 18 than for biotypes 1 and 2.…”
Section: Resultssupporting
confidence: 90%
“…Based on the results of sensitivity testing studies published to date in the literature, the susceptibility of M. odoratimimus to various classes of antibiotics appears to mirror that of M. odoratus, but at a lower level [24][25][26][27]. Actually, the strain isolated from our patient retained susceptibility only to carbapenems and antipseudomonal penicillins, and was resistant to all other b-lactams tested (including aztreonam), as well as to aminoglycosides, quinolones, and trimethoprim/sulfamethoxazole.…”
Section: Discussionmentioning
confidence: 75%
“…The treatment of Myroides infection is often difficult, since most strains are resistant to the b-lactams, including aztreonam and carbapenems, and exhibit variable susceptibility to aminoglycosides, quinolones, and sulfamethoxazole [24][25][26]. Based on the results of sensitivity testing studies published to date in the literature, the susceptibility of M. odoratimimus to various classes of antibiotics appears to mirror that of M. odoratus, but at a lower level [24][25][26][27].…”
Section: Discussionmentioning
confidence: 92%
“…The respiratory tract, however, is the most common site of infection, and the incidence of these infections is on the increase (from 2.5% in 1998 to 4.1% in 1999) [30,31]. S. maltophilia is intrinsically resistant to many commonly used antimicrobial agents and rapid selection of high-level multidrug-resistant isolates in clinical strains has been observed [39,40]. S. maltophilia isolates produce a number of inducible enzymes, such as L1 (Bush group 3) zinc-dependent carbapenemase and L2 (Bush Group 2e) cephalosporinase, which hydrolyze important classes of ␤-lactams such as carbapenems and cephalosporins, respectively [41,42].…”
Section: Introductionmentioning
confidence: 98%